Sugar birds : a novel - Bostrom, Cheryl (Tyndale House Publishers, 2023)
"Northwest Washington State, 1985 For years, Harris Hayes has taught his daughter, Aggie, the ways of the northern woods. So when her mother's depression worsens, Harris shows the girl how to find and sketch the nests of wild birds as an antidote to sadness. Aggie is in a tree far overhead when her unpredictable mother spots her and forbids her to climb. Angry, the ten-year-old accidentally lights a tragic fire, then flees downriver. She lands her boat near untamed forest, where she hides among the trees and creatures she considers her only friends-determined to remain undiscovered. A search party gathers by Aggie's empty boat hours after Celia, fresh off the plane from Houston, arrives at her grandmother's nearby farm. Hurting from her parents' breakup, she also plans to run. But when she joins the hunt for Aggie, she meets two irresistible young men who compel her to stay. One is autistic; the other, dangerous. Perfect for fans of Under the Magnolias, Where the Crawdads Sing, and The Great Alone, Sugar Birds immerses readers in a layered, evocative coming-of-age story set in the breathtaking natural world where characters encounter the mending power of forgiveness-for themselves and for those who have failed them"--